Classical Activation of Macrophages Leads to Lipid Droplet Formation Without de novo Fatty Acid Synthesis - Rosas-Ballina, Mauricio; Guan, Xue Li; Schmidt, Alexander; Bumann, Dirk (Frontiers in Immunology, 2020)
Altered lipid metabolism in macrophages is associated with various important inflammatory conditions. Although lipid metabolism is an important target for therapeutic intervention, the metabolic requirement involved in lipid accumulation during pro-inflammatory activation of macrophages remains incompletely characterized. We show here that macrophage activation with IFNγ results in increased aerobic glycolysis, iNOS-dependent inhibition of respiration, and accumulation of triacylglycerol. Surprisingly, metabolite tracing with 13C-labeled glucose revealed that the glucose contributed to the glycerol groups in triacylglycerol (TAG), rather than to de novo synthesis of fatty acids. This is in stark contrast to the otherwise similar metabolism of cancer cells, and previous results obtained in activated macrophages and dendritic cells. Our results establish a novel metabolic pathway whereby glucose provides glycerol to the headgroup of TAG during classical macrophage activation.